2018
DOI: 10.1101/391094
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial dynamics within and between brain functional domains: A hierarchical approach to study time-varying brain function

Abstract: The analysis of time-varying connectivity in functional magnetic resonance imaging (fMRI) has become an important part of ongoing neuroscience discussions. The majority of such studies have focused primarily on temporal variations of functional connectivity among fixed regions of interest (ROIs) or networks of the brain. However, the brain reorganizes its activity on both temporal and spatial scales.Thus an approach which captures time-varying characteristics of brain functional organizations is essential to i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…At the network level, networks that are engaged in a wide range of cognitive functions, such as the FPN, seem to have the highest level of dynamism (Zalesky et al, 2014;Iraji et al, 2019b). The relevance of dFC is also supported by other studies that evaluate the relationship between dFC properties and biological features such as age, gender, and cognitive processes (Thompson et al, 2013a;Leonardi et al, 2014;Elton and Gao, 2015;Hutchison and Morton, 2015;Qin et al, 2015;Yaesoubi et al, 2015a;Yaesoubi et al, 2015b;Shine et al, 2016a;Shine et al, 2016b;Kucyi et al, 2017;Kucyi, 2018).…”
Section: Dynamic Functional Connectivity (Time-varying Functional Patmentioning
confidence: 73%
See 3 more Smart Citations
“…At the network level, networks that are engaged in a wide range of cognitive functions, such as the FPN, seem to have the highest level of dynamism (Zalesky et al, 2014;Iraji et al, 2019b). The relevance of dFC is also supported by other studies that evaluate the relationship between dFC properties and biological features such as age, gender, and cognitive processes (Thompson et al, 2013a;Leonardi et al, 2014;Elton and Gao, 2015;Hutchison and Morton, 2015;Qin et al, 2015;Yaesoubi et al, 2015a;Yaesoubi et al, 2015b;Shine et al, 2016a;Shine et al, 2016b;Kucyi et al, 2017;Kucyi, 2018).…”
Section: Dynamic Functional Connectivity (Time-varying Functional Patmentioning
confidence: 73%
“…Interestingly, regions with different cognitive and processing demands represent different levels of dynamism. The brain networks/areas that are known to be involved in higher cognitive processing show a higher level of dynamism measured by dFC than networks/areas engaged in primary processing (Zalesky et al, 2014;Chen et al, 2016;Iraji et al, 2019b).…”
Section: Dynamic Functional Connectivity (Time-varying Functional Patmentioning
confidence: 99%
See 2 more Smart Citations
“…Using SWPC, Damaraju et al, found that SZ compared to TC tend to stay less in states which shows strong overall connectivity while they tend to spend more time in states showing weak connectivity between different domains . Other studies also reported transient reductions in both functional connectivity and networks activities (Iraji, et al, 2019a;Iraji, et al, 2019b). Miller et al, reported less dynamism (e.g.…”
Section: Schizophrenia-related Findingsmentioning
confidence: 95%